Specification of a Model for the Study of Reproductive Choice (Global Journal of Management and Business Research, 2019)
The discussion and specification of a model for the study of reproductive choice was the objective of this paper. A documentary study was carried out with an intentional selection of sources indexed to Dialnet, Latindex, Publindex, Redalyc and Scielo from 1961 to 2019. The relationship between the calculation of costs and benefits with risk behaviors was established, although the design of the investigation limited the discussion with the consulted literature, suggesting the extension of the work from the information published in Copernicus, Ebsco, Scopus and WoS.
Keywords: sexual health; reproductive health; rational choice; interruption of pregnancy